The role of virtual reality haptic technology in dental education: A systematic review - Abraari, Mohammad Agiel; Syawqie, Achmad; Nur'aeny, Nanan (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2025)
ABSTRAKIntroduction: Dental students are required to develop strong clinical motor skills, but conventional training tools such as mannequins often lack realistic sensory feedback. Haptic virtual reality (VR) technology offers a modern solution by providing tactile simulation, though its effectiveness compared to traditional methods remains unclear. This study aims to evaluate the effectiveness of haptic VR in improving motor skills, knowledge, and confidence among dental students. Methods: A systematic review was conducted following PRISMA guide lines, including RCT or observational studies on haptic VR in dental education from PubMed, Scopus, and ScienceDirect databases. Data were analyzed narratively due to study heterogeneity. Results: A total of 12 studies show that haptic VR is effective for training procedures such as caries preparation, scaling, veneer preparation, and pulpotomy. Students demonstrated improved hand-eye coordination, procedural understanding, and confidence. However, effectiveness depends on device quality, user experience, and integration into the curriculum. Conclusions: Haptic VR cannot fully replace traditional methods but serves as a valuable complementary tool, especially in endodontics, periodontics, and as a supplementary aid in conservative dentistry, prosthodontics, and pediatric dentistry.KEY WORDS: haptic virtual reality, motoric skill, dentistryPeran teknologi haptic virtual reality dalam pendidikan kedokteran gigi: Ulasan sistematikABSTRACTPendahuluan: Mahasiswa kedokteran gigi membutuhkan keterampilan motorik klinis yang baik, namun pelatihan konvensional seperti manekin memiliki keterbatasan dalam memberikan umpan balik sensorik. Teknologi haptic virtual reality (VR) menawarkan solusi modern dengan stimulasi taktil yang realistis, namun efektivitasnya masih perlu dikaji secara sistematis. Studi ini bertujuan mengevaluasi efektivitas haptic VR dalam meningkatkan keterampilan motorik, pengetahuan, dan kepercayaan diri mahasiswa. Metode: Penelitian menggunakan metode systematic review dengan pedoman PRISMA, mencakup artikel RCT atau observasional mengenai haptic VR dalam pendidikan kedokteran gigi dari database PubMed, Scopus, dan ScienceDirect. Analisis dilakukan secara naratif karena heterogenitas studi. Hasil: Terdapat 12 artikel yang menunjukkan haptic VR efektif dalam pelatihan prosedur seperti preparasi karies, scaling, veneer, dan pulpotomi. Mahasiswa mengalami peningkatan koordinasi tangan-mata, pemahaman prosedur, dan kepercayaan diri. Efektivitas dipengaruhi oleh kualitas perangkat, pengalaman pengguna, dan integrasi dalam kurikulum. Simpulan: haptic VR belum menggantikan metode tradisional, namun berpotensi sebagai alat bantu yang efektif, khususnya dalam pelatihan endodontik, periodontik, konservasi, prostodontik, dan kedokteran gigi anak.KATA KUNCI: haptic virtual reality, keterampilan motorik, pendidikan kedokteran gigi